Siti Mahfudho Konsep Istiqomah dalam Kitab Riyadh Ash-Sholihin karya Imam An-Nawawi dan Relevansinya dengan Tujuan Pendidikan Islam - Fudhe, Siti Mahfudho; Moh. Solehuddin; Nanang Abdillah (Risda: Jurnal Pemikiran dan Pendidikan Islam, 2023)
The main goal of Islamic education is the formation of morals and good manners that are capable of producing people who are moral, have a clean spirit, never give up, have high aspirations, and have noble character, and can distinguish between good and bad, avoid despicable acts, remembering God, and knowing in every work done. This study uses a qualitative description approach. The type of research is Library Research or literature. The data in this research are in the form of books, notes and words summarized in the book Riyad Ash-Sholihin. In collecting data, researchers used content analysis techniques and conclusions (verification). The results of the study can be concluded that there are two relevance to the goals of Islamic education. Second, the deeds that are loved by Allah azza wa jalla which are done in accordance with the sunnah, simple, easy, and takalluf (self-incriminating) in doing.